Finding Use for Sorghum Bicolor Leaf Sheath in Coating Technology - Isaac, Johnson Ajeh; Fasuba, Kayode Ilesanmi (Pharmaceutical Fronts, 2021)
This study aimed to investigate the potential use of aqueous extract of Sorghum bicolor leaf sheath (SBLS) as a coating agent for paracetamol tablets. The mechanical properties of the coated tablets were assessed using crushing strength and friability test, while the release properties of the tablet were evaluated using disintegration and dissolution tests. The physicochemical properties of the coated tablets did not show any striking differences when compared with the uncoated tablet as par compendium specifications, which formed the basis for performing further in vitro dissolution study. Our data showed that SBLS enhanced the hardness and friability of the tablets in a dose-dependent manner. Tablets coated with 3, 5, and 7.5% of SBLS disintegrated in 8.13, 6.25, and 4.13 minutes, respectively, while the uncoated tablet disintegrated in 0.7 minutes. Furthermore, 3, 5, and 7.5% of SBLS-coated tablets exhibited slower release of their active ingredient (releasing 21, 16, and 17%, respectively) than that of the uncoated tablet (releasing 40%) in 5 minutes. Besides, comparison between the dissolution profiles was successfully achieved using difference factor (f1) and similarity factor (f2). The apparent dissimilarity between our coated tablets and the uncoated one led to further study of convolution in vitro–in vivo correlation, with the aim to obtain data that converted into mathematical prediction of in vivo data. For all batches, the percent predictable errors of Cmax and Tmax were within the acceptable limit of no more than 10%. In summary, SBLS aqueous extract is a potential and protective coat agent for paracetamol tablets. The in vitro established dissolution of the coated tablets provided scientific information for the prediction of the in vivo plasma drug profile.
Keywords: Sorghum bicolor leaf sheath; coat agent; paracetamol tablet; in vitro–in vivo correlation